EPIDURAL DEXAMETHASONE FOR POST-OPERATIVE ANALGESIA IN PATIENTS UNDERGOING INFRAUMBILICAL SURGERIES - SONALI A JOSHI; DAISY S GAJJAR (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study was designed to evaluate the effect of adding dexamethasone to epidural bupivacaine for post-operative analgesia in infraumbilical surgeries. This study aimed to evaluate the efficacy of epidural dexamethasone used as an adjuvant to bupivacaine to compare sensory and motor block characteristics, intraoperative hemodynamic parameters, duration of post-operative analgesia, and any side effects of study drugs in both the groups. Methods: Seventy-two patients undergoing any infraumbilical surgeries were divided into the following two groups. (1) Group D (n=36): 18 mL of isobaric bupivacaine 0.5% and 2 mL (8 mg) of dexamethasone given epidurally and (2) Group B (n=36): 18 mL of isobaric bupivacaine 0.5% and 2 mL of normal saline given epidurally. Intraoperative hemodynamic parameters, onset, and duration of sensory and motor blockade, two-segment regression time, and duration of post-operative analgesia were assessed. Results: The time of onset of sensory and motor blockage was faster in the dexamethasone group as compared to the control group (p<0.05). The time taken to achieve the T10 sensory block was comparatively shorter in Group D compared to Group B (p<0.001). Duration of analgesia was markedly prolonged in the dexamethasone group (p<0.001). One patient (0.36%) in the dexamethasone group and five patients (13.88%) in the control group had nausea (p>0.05). None of our patients had vomiting in the two groups. Conclusion: The study showed that adding dexamethasone to bupivacaine (0.5%) epidurally shortened the onset of sensory and motor block, reduced post-operative visual analog scale score, prolonged the duration of analgesia with hemodynamic stability and minimum side effects.